Documented Experiences among Food Service Businesses towards Future-Proofing the Industry - Bahillo, Eloiza Loren (JPAIR Multidisciplinary Research, 2022)
Food service businesses such as restaurants and catering services encountered challenges during and after the Covid-19 Pandemic. This quasi-phenomenological qualitative research approach documented the idiosyncratic experiences of Food Service Business Owners and Managers during the Covid-19 Pandemic, determined the challenges encountered by the Food Service Business Owners and Managers, identified the measures implemented by Food Service Industry during and after the Covid-19 Pandemic, and a recommended future-proofing framework in the Food Service Business. The researcher interviewed the selected Registered Food Service Businesses in the economic center of the Second District of Albay, Philippines using an open-ended interview questionnaire and presented a consent form to the participants for it to be recorded and documented. Scrutinized data have determined that the point of view and experiences of the Food Service Business Owners and Managers were relatively comparable. Consequently, Food Service Business Owners and Managers would always be willing to adjust to the current situation or to any business disruption that may occur, particularly on the demands of their customers, by adopting the technological trends, which means having a digital platform to continuously cater to their queries and orders.
Keywords: Business and Management; food service business; future-proofing framework; covid-19 pandemic; business disruption; quasi-phenomenological qualitative; Philippines